2019
DOI: 10.1371/journal.pone.0215075
|View full text |Cite
|
Sign up to set email alerts
|

Post-exposure administration of chimeric antibody protects mice against European, Siberian, and Far-Eastern subtypes of tick-borne encephalitis virus

Abstract: Tick-borne encephalitis virus (TBEV) is the most important tick-transmitted pathogen. It belongs to the Flaviviridae family and causes severe human neuroinfections. In this study, protective efficacy of the chimeric antibody chFVN145 was examined in mice infected with strains belonging to the Far-Eastern, European, and Siberian subtypes of TBEV, and the antibody showed clear therapeutic efficacy when it was administered once one, two, or three days after infection. The efficacy was indep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 32 publications
1
11
0
Order By: Relevance
“…In the case of the ch14D5 antibody, it was shown that it is able to bind to the D3 domain at a reduced pH value (pH 4.8, which is even more acidic than pH ~ 5.0 inside of late endosomes) almost as strongly as at physiological pH 7.2 (FigureS6). Our hypothesis that the ch14D5 antibody can block infection at the post-attachment step is in good agreement with the fact that this antibody, as well as the related chFVN145 antibody, did not induce ADE in in vivo experiments(Baykov IK et al, 2014;Matveev AL et al, 2019). At the moment, experimental structures are only available for three antibodies against TBEV: 19/1786 (Fuzik T et al, 2018), Mab 4.2 (Yang X et al, 2019) and T025 (Agudelo M et al, 2021).…”
supporting
confidence: 87%
See 1 more Smart Citation
“…In the case of the ch14D5 antibody, it was shown that it is able to bind to the D3 domain at a reduced pH value (pH 4.8, which is even more acidic than pH ~ 5.0 inside of late endosomes) almost as strongly as at physiological pH 7.2 (FigureS6). Our hypothesis that the ch14D5 antibody can block infection at the post-attachment step is in good agreement with the fact that this antibody, as well as the related chFVN145 antibody, did not induce ADE in in vivo experiments(Baykov IK et al, 2014;Matveev AL et al, 2019). At the moment, experimental structures are only available for three antibodies against TBEV: 19/1786 (Fuzik T et al, 2018), Mab 4.2 (Yang X et al, 2019) and T025 (Agudelo M et al, 2021).…”
supporting
confidence: 87%
“…These factors also affect whether a particular antibody is prone to cause undesirable antibody-mediated enhancement (AME) of infection or not (Pierson TC et al, 2007;Pierson TC et al, 2008;Dowd KA et al, 2011). Several neutralizing or protective monoclonal antibodies have previously been described against TBEV (Guirakhoo F et al, 1989;Mandl CW et al, 1989;Holzmann H et al, 1995;Tsekhanovskaya NA et al, 1993;Levanov LN et al, 2010;Kiermayr S. et al, 2009;Matveev AL et al, 2019;Agudelo M et al, 2021). However, the 3D structures of the antigen-antibody complex have only been published for three of them: 19/1786, Mab 4.2 and T025 (Niedrig M et al 1994;Fuzik T et al, 2018;Jiang W et al, 1994;Yang X et al, 2019;Agudelo M et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Recombinant antibodies are one of the promising types of medicines against flaviviruses, TBEV in particular [ 15 , 22 , 23 , 24 ]. Several antibodies against TBEV have been obtained [ 43 , 44 , 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recombinant antibodies are promising medicines against flaviviruses, including TBEV [ 15 , 22 , 23 , 24 ]. The chimeric antibody ch14D5 has been previously constructed and characterized [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…A more recent study investigating TBEV neutralization in vitro and in mice by treatment with intravenous immunoglobulins containing high amount of TBEV-specific neutralizing antibodies supports these findings since no ADE was observed by the application of cross-reactive or virus-specific antibodies at different neutralization levels [ 148 ]. In vivo investigations in mice with sub-neutralizing concentrations of a chimeric antibody against EDIII containing the constant regions of human IgGκ (chFVN145), proposed as post-exposure treatment, also showed no indications of ADE for the three main TBEV subtypes [ 149 ]. Additionally, in vivo and in vitro studies addressing the potential effect of TBEV-specific immunity on ZIKV infection suggested that humoral immunity against TBEV is unlikely to contribute to enhancement of ZIKV-induced pathogenesis in humans [ 150 ].…”
Section: Immune Response To Tbev Infection and Vaccinationmentioning
confidence: 99%